Modifying an Open Science Online Grocery for parents of youth with anorexia nervosa: A proof‐of‐concept study. Issue 5 (3rd February 2023) - Makara, Amanda; Howe, Holly; Cooper, Marita; Heckert, Kerri; Weiss, Samantha; Kellom, Katherine; Scharf, Danielle; Ubel, Peter; Orloff, Natalia; Timko, C. Alix
Abstract: Objective: For youth with anorexia nervosa (AN), remission requires high caloric goals to achieve weight restoration, consumption of a wide variety of calorically dense foods, and reintroduction of eliminated foods. Family‐based treatment (FBT), the gold‐standard treatment for youth with AN, empowers parents to renourish their child and restore them to health; yet, parents often report struggling with shifting meal planning and grocery shopping behaviors to focus on nutritional rehabilitation and weight restoration. Methods: This proof‐of‐concept study aimed to modify a simulated grocery store (Open Science Online Grocery [OSOG]) for parents of youth with AN and explore the acceptability and feasibility of its use as part of standard care. Study staff collaborated with six parent research partners to modify the OSOG prior to piloting it with participants. Participants were 10 parents of youth undergoing a first‐time hospitalization for medical stabilization of AN or atypical AN. Parents completed a battery of measures and a semistructured interview assessing the acceptability and feasibility of OSOG. Results: Parents described the tool as credible and acceptable. Qualitative feedback highlighted common themes of caregiver burden, nutrition education, and acceptability of the tool. Discussion: Results point to the need for more work in supporting parents in Phase I of FBT. Public Significance: Families are instrumental in supporting youth to recover from anorexia nervosa. During treatment, parents are charged with selecting and serving their adolescent's meals, often requiring them to change grocery shopping and food preparation habits to meet their child's high caloric needs. Parents reported feeling overwhelmed by this task and noted struggling with learning different approaches to nourish their adolescent during an already stressful time. Collaboratively with parents, we modified a tool to support parents in shifting thier shopping habits, which they reported as being a helpful springboard in the early phase of treatment.